An investigation of the factors contributing to limited growth in youth informal sector businesses in Masvingo Province: a case Study of Zaka District. - Kakono, Tafirenyika (Midlands State University, 2020)
This study was a contribution to the limited literature and knowledge on the performance of the rural informal sector businesses. The study sought to conduct an investigation of the factors contributing to limited growth in youth informal sector businesses in Masvingo Province: A Case Study of Zaka District. The study was motivated by the understanding that the informal sector was viewed as having great potential for employment creation and driving economic development. The investigation was conducted using a qualitative Case Study design and data was collected using the following research instruments; in-depth interview guides, observation, Focus Group Discussion (FGD) and Key Informant Interviews (KII). Literature at international, regional, and national levels was reviewed to provide insights in to knowledge that existed as well as gaps that required attention. The conclusions from the study were that; there was limited growth of youth informal sector businesses in Zaka and hence youth unemployment remained very high. The informal sector businesses required a lot of support to address the infrastructural, environmental and behavioural and, or perceptional challenges affecting business growth. Lack of appreciation of the potential of the informal sector to create employment and drive the economy by stakeholders affected support to the sector. Youth engaged in more consumption than re-investment activities and hence needed capacity development to address that negative behaviour. Stakeholders had more influence on types of businesses youth participated in and this was less sustainable. There were limited financial resources circulating in the informal sector businesses in Zaka. Limited but quality support was given to youth businesses leading to quality business decisions by the youth. Youth support needs were diverse and hence required well-coordinated, multidisciplinary approach. The conclusions meant that holistic support was needed for rural informal sector businesses to unlock their potential for employment creation and economic development.